Reforming and promoting local agricultural markets: a research approach - Badiane, Ousmane; Nuppenau, Ernst-August (International Food Policy Research Institute, 1997)
Although the techniques that are being used have become much more sophisticated, recent methodological developments in market research have hardly gone beyond the econometric test of market integration. While more efficient methods are being proposed to analyze price interdependence, the implications at the farm level and for agricultural transformation are not part of the analysis. However, one would expect reforming governments to be more interested in issues such as i) the implications of market integration for the operation of local markets, ii) its impact on the process of domestic market reforms, iii) strategies to improve the degree of integration, and iv) the benefits of doing so. It is well known that the ultimate impact at the local level of changes in macroeconomic policies depend to a large extent on the adjustment at the meso-level, meaning the marketing sector. Consequently, understanding the impact of economic policy reforms at the local level requires an integrated approach to analyzing macroeconomic and marketing policy changes. The present paper develops a model which, while starting from the integration approach, offers an extension of the latter to show the implication of market integration for the adjustment of local markets to policy reforms.